Remnant cholesterol is associated with poor prognosis in patients with hepatitis B-related acute-on-chronic liver failure: a Chinese population-based study - Juan Liu; Yuna Wang; Songsong Yuan; Jiwei Fu; Wentao Zhu (Lipids in Health and Disease)
Abstract Background Hepatitis B-related acute-on-chronic liver failure (HBV-ACLF) patients possess adverse lipid homeostatic alterations, subsequently affecting their treatment regimens and prognoses. However, the precise association between one lipid homeostasis indicator, remnant cholesterol (RC), and HBV-ACLF prognoses have not been fully elucidated. In this retrospective study, the relationship between RC with 28- and 90-day HBV-ACLF prognoses was delineated. Methods 595 HBV-ACLF patients were recruited, and data collected for laboratory parameters at admission, as well as whether poor 28- and 90-day prognoses occurred during the follow-up period, in the form of mortality, or liver transplantation. Patients were divided into 3 groups, based on RC tertiles (Q1-3), and 4 multivariate Cox regression analyses were conducted to identify the associations between RC levels and ACLF prognoses; these analyses excluded different confounding factors, based on the Strengthening the Reporting of Observational Studies in Epidemiology statement. Stratified analysis was conducted to investigate the association between RC and ACLF risk among different subgroups, based on age, sex as well as complications and artificial liver treatment. RC accuracy versus that of other lipid indicators to predict 28- and 90-day ACLF survival was evaluated by restricted cubic spline and receiver operating characteristic (ROC) curve analyses, while Kaplan-Meier curves measured cumulative 28- and 90-day mortality risks. Results For all 4 regression models, higher RC were associated with worse liver function, coagulation, and HBV-ACLF prognoses. Restricted cubic spline analysis identified a non-linear relationship between RC and HBV-ACLF prognoses, in which the Q3 RC tertile had the lowest 28-day and 90-day HBV-ACLF survival rates; this was further confirmed by Kaplan-Meier analysis. Additionally, subgroup analysis found that higher RC correlated to worse ACLF prognoses among hypoproteinemia patients. Moreover, RC, compared to total cholesterol, triglycerides, high- and low-density lipoprotein cholesterol, as well as non-high density lipoprotein, was the most accurate in predicting poor 28- and 90-day ACLF prognoses. Conclusions Elevated RC was significantly associated with poorer 28- and 90-day HBV-ACLF prognoses, even after accounting for all other traditional risk factors. Therefore, monitoring RC, along with interventions to reduce their levels, could aid in improving ACLF patient outcomes.